A novel temozolomide analog, NEO212, with enhanced activity against MGMT-positive melanoma in vitro and in vivo. Issue 2 (28th March 2015) - Chen, Thomas C.; Cho, Hee-Yeon; Wang, Weijun; Nguyen, Jenny; Jhaveri, Niyati; Rosenstein-Sisson, Rachel; Hofman, Florence M.; Schönthal, Axel H.
Highlights: Temozolomide was modified by conjugation to perillyl alcohol. The resulting novel analog, NEO212, exerted superior activity against melanoma. NEO212 was also active against drug-resistant tumors in vivo. NEO212 should be developed for clinical use. Abstract: The alkylating agent temozolomide (TMZ) represents an important component of current melanoma therapy, but overexpression of O6-methyl-guanine DNA methyltransferase (MGMT) in tumor cells confers resistance to TMZ and impairs therapeutic outcome. We investigated a novel perillyl alcohol (POH)-conjugated analog of TMZ, NEO212, for its ability to exert anticancer activity against MGMT-positive melanoma cells. Human melanoma cells with variable MGMT expression levels were treated with NEO212, TMZ, or perillyl alcohol in vitro and in vivo, and markers of DNA damage and apoptosis, and tumor cell growth were investigated. NEO212 displayed substantially greater anticancer activity than any of the other treatments. It reduced colony formation of MGMT-positive cells up to eight times more effectively than TMZ, and much more potently induced DNA damage and cell death. In a nude mouse tumor model, NEO212 showed significant activity against MGMT-positive melanoma, whereas TMZ, or a mix of TMZ plus POH, was ineffective. At the same time, NEO212 was well tolerated. NEO212 may have potential as a more effective therapy for advanced melanoma, and should become particularly suitable for the treatment of patients with MGMT-positive tumors.